La sociedad filmada. Apuntes sobre la historia del Perú a partir de tres películas - Valdez Morgan, Jorge Luis (2005)
This article analyzes, from the perspective of social history, three films which may be considered paradigmatic of Peruvian film-making: Yo perdí mi corazón en Lima (I lost my heart in Lima, 1933), Kukuli (1961), and Muerte al amanecer (Death at Dawn, 1977). The analysis is based on the theoretical postulatesof Marc Ferro and the Cinematic Contextual History. Currently, movies constitute an important source for studying contemporary history, although they have been used very little by researchers who are interested in the history of Peru. This article aims to fill in that vacuum.